Analisis Risiko Terhadap Waktu dan Biaya pada Struktur Bawah Proyek Pembangunan Gedung Kejaksaan Tinggi Jakarta - Abdul Fakar Hidayat Naypon; Hikma Dewita (Universitas Islam Lamongan, 2022)
The implementation of construction project work is inseparable from a risk, the risk can be detrimental and have an impact on project achievement, as well as the Jakarta High Prosecutor's Office Building project. This study aims to determine the risk factors, the level of risk and the dominant risk in the work of the lower structure of the construction project. The data is processed using the Analytic Hierarchy Process (AHP) method to obtain the risk weight. The analysis process is in the form of distributing the first questionnaire, namely the relevant test questionnaire and followed up on the second questionnaire, namely the probability x impact questionnaire on time and cost. The analysis results obtained, 34 relevant risks, from the 34 relevant risks, 6 dominant risks and those that impact costs were obtained, these risks were Landslides, Inaccurate soil data, Error in determining point and foundation dimensions, Marking errors, Energy productivity work not as expected, Weak time control system. Therefore, from the results of the analysis it can be concluded that in the implementation of the construction of the Jakarta High Prosecutor's Office there are 3 risks, namely the risk of marking errors, the risk of labor productivity not according to estimates and the risk of a weak time control system, which dominantly affects time and cost and has a possible weight. highest occurrence.